Evaluation of the full set of habitat suitability models for vulnerable marine ecosystem indicator taxa in the South Pacific high seas - Matthew Bennion; Owen F. Anderson; Ashley A. Rowden; David A. Bowden; Shane W. Geange; Fabrice Stephenson (Fisheries Management and Ecology, 2024)
In the high seas, regional fishery management organisations are required to implement measures to prevent significant adverse impacts on vulnerable marine ecosystems (VMEs). Our objectives were to develop habitat suitability models for use in the spatial management of bottom fisheries in the South Pacific and to evaluate these and existing models using independent data from high‐quality seafloor imagery. Presence‐only models for seven VME indictor taxa were developed to complement previous modelling. Evaluation of habitat suitability models using withheld data indicated high mean True Skill Statistic scores of 0.44–0.64. Most habitat suitability models performed adequately when assessed with independent data on taxon presence and absence but were poor surrogates for abundance. We therefore advocate caution when using presence‐only models for spatial management and call for more systematically collected data to develop abundance models.